Konten Akun TikTok Nadiraa Hijab dalam Perspektif Wanita Muslim - Nadia, Kholimatus; Abdurrazak, Abdurrazak (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Young Muslim are starting to be interested in buying hijab or clothing products that they see on the TikTok platform because of the visual content that is displayed with its own uniqueness, besides that they are Muslim women who follow fashion trends, as well as Muslim women who try. Follow the trend by using the hijab. One of the TikTok accounts that has a hijab shop in Yogyakarta and always updates its content with products that are currently hits, namely the @Nadiraa-hijab account. The results of observations with rational choice theory glasses, on the @Nadiraa-hijab account, found at least 5 reasons why consumers are interested in buying products from Nadir’s store which they watch through videos on the TikTok platform. Among them are the uniqueness and novelty of video content whose products follow trends, the use of numbers in product endorsements, then the price and quality of goods sold by Nadiraa’s store on his TikTok account @Nadiraa-hijab, then ease of purchase and finally the emotional connection berween fellow communities is built. On social media is judged by the number of likes and comments on the @Nadiraa-hijab assount. Judging from customer comments on Nadiraa’s TikTok account, that they are very happy with the products offered because they are in accordance with the fashion trends of today’s young people, who wear hijab starting from an interest in following fashionable trends, or indeed wearing hijab because they follow shariah in Islam.